The significance of PAK4 in signaling and clinicopathology: A review - Yu Xinbo; Huang Changwei; Liu Jiyuan; Shi Xinyu; Li Xiaodong (Open Life Sciences, 2022)
P21-activated protein kinases (PAKs) are thought to be at the center of tumor signaling pathways. As a representative member of the group II PAK family, P21-activated protein kinase 4 (PAK4) plays an important role in the development of tumors, with several biological functions such as participating in oncogenic transformation, promoting cell division, resisting aging and apoptosis, regulating cytoskeleton and adhesion, as well as suppressing antitumor immune responses. PAK4 is also crucial in biological processes, including the occurrence, proliferation, survival, migration, invasion, drug resistance, and immune escape of tumor cells. It is closely related to poor prognosis and tumor-related pathological indicators, which have significant clinical and pathological significance. Therefore, this article offers a review of the structure, activation, and biological functions of PAK4 and its clinical and pathological importance. This overview should be of assistance for future research on PAK4 and tumors and provide new ideas for tumor treatment and prognostic evaluation of patients.